2021
DOI: 10.1159/000514454
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Interleukin-2 Receptor Antagonist Induction Therapy in Standard-Risk Renal Transplant Recipients Maintained on Tacrolimus: A Systematic Review and Meta-Analysis

Abstract: <b><i>Introduction:</i></b> The additive benefit of interleukin-2 receptor antagonist (IL2-RA) induction in standard-risk kidney transplant recipients, while maintained on tacrolimus-based immunosuppressive therapy, is uncertain. <b><i>Methods:</i></b> We divided the studies included in this meta-analysis into 2 groups: group A (included studies that used same dose of tacrolimus in both arms of each study) and group B (included studies that compared patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, in more recent studies utilizing modern immunosuppression, IL2RA induction has not demonstrated similar benefits compared to no induction. IL2RA induction was not associated with a rejection benefit at 6 months or graft survival benefit at 1‐year in a large meta‐analysis 18 . Similarly, a registry analysis using data from the British Renal Transplant Registry did not find that IL2RA induction affected eGFR or graft outcomes at 1‐year 19 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in more recent studies utilizing modern immunosuppression, IL2RA induction has not demonstrated similar benefits compared to no induction. IL2RA induction was not associated with a rejection benefit at 6 months or graft survival benefit at 1‐year in a large meta‐analysis 18 . Similarly, a registry analysis using data from the British Renal Transplant Registry did not find that IL2RA induction affected eGFR or graft outcomes at 1‐year 19 …”
Section: Discussionmentioning
confidence: 96%
“…IL2RA induction was not associated with a rejection benefit at 6 months or graft survival benefit at 1-year in a large meta-analysis. 18 Similarly, a registry analysis using data from the British Renal Transplant Registry did not find that IL2RA induction affected eGFR or graft outcomes at 1-year. 19 Our study also examined only low immunologic risk patients.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, there was significant difference in PRA levels between basiliximab and thymoglobulin groups. However, the PRA levels in both groups were less than 10%, which is considered as the cut-off for standard immunological risk transplants in most of the literature [ 5 , 9 ]. In addition, we included patients with no previous transplants in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a statistical difference between both induction groups in terms of donor age. However, from the clinical point of view, both ages (44.73 in the thymoglobulin group and 47.82 in the basiliximab group) are very similar and do not meet the criteria for expanded criteria donor [ 5 , 13 ]. Our results reflect that selection of living donors with age less than 50 leads to acceptable transplant outcomes irrespective of HLA mismatching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation